THE EXPLOITATION OF THE ESTUARIES IN THE KENDAL AREA (NORTHERN COAST OF JAWA) BY ARTISANAL FISHERMEN - Hadikoesworo, Harjadi (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
The estuaries at the northern coast of Jawa are good fishing grounds for the artisanal fishermen. They have been exploited heavily, and is becoming more so with the advance of technology in the form of motorized vessels. Does the exploitation provide a good livelihood to the fishermen? The outcome of the preliminary analysis of the fishing activities of artisanal fishermen in the Kendal area (Central Jawa) will be presented, the problems discussed.